Bibliometric Review in the Scope of Administration and Education: Alternative Methods for Conflicts Resolution (Revista Direito em Debate, 2022)
The objective of the article is to demonstrate scientific publications on alternative methods of conflict resolution in Brazil and in the world, throughout the period existing in the research bases and in recent years, restricting the research to categories related to Administration, related areas and Education. A survey of the scientific production of the alternative expression of dispute resolution was carried out during the entire period existing in the Web of Science database and also over the last 11 years (2010-2021), in order to make a comparison possible. Afterwards, the research was carried out in the Electronic Library of Scientific Journals (Spell), to learn about research in Brazil on the topic of conflict resolution. The VOSviewer software was also used to create a word map. It was found that at the national level publications on the subject are still scarce, as only five scientific articles were located. At the international level, the theme has a greater impact on publications. According to the comparative analysis carried out between the entire period of the base and the years 2010 to 2021, similarity is evident in all results. At the end of this bibliometric research, it was possible to outline an overview of what is being researched at national and international level on alternative conflict resolution in the area of ​​Administration and related issues, as well as in the area of ​​education, contributing to the publication of new works on the theme,Keywords: alternative conflict resolution methods; conflict resolution; alternative dispute resolution; bibliometric review.